Threats and Opportunities For Textile and Other Textile Products (TPT) in The Efta Market Using The Indonesia-Efta Scheme - Arvina, Kayla Putri (Riviera Publishing, 2024)
This thesis examines the problems and opportunities faced by the Indonesian textile and textile products (TPT) industry in the European Free Trade Association (EFTA) market through implementing the Indonesia-EFTA scheme. The analysis tool used is Revealed Comparative Advantage (RCA), which allows the detection of relative comparative advantages in Indonesia's textile exports to the EFTA market. The report highlights various important aspects that affect Indonesia's textile competitiveness in the market, including trade rules, quality requirements, and consumer trends. The results of the RCA analysis provide in-depth insight into the relative position of Indonesian TPT in the EFTA market, as well as the potential for sector development in the context of the Indonesia-EFTA trade agreement. These findings can provide a framework for government policies and business strategies for textile industry players to take advantage of opportunities and address challenges in strengthening their competitiveness in the EFTA market.